Determinant Factors of Exclusive Breastfeeding in the Work Area - Khasanah, Umi; Piskanoni, Ainun; Ropitasari, Ropitasari (Universitas Muhammadiyah Semarang, 2025)
Exclusive breastfeeding is recommended for 6 months, however exclusive breastfeeding in several regions in Indonesia is still below the target set by the government. This condition is caused by exclusive breastfeeding being influenced by several factors such as work, education, age and husband’s support. Objective to analyze the determinants of exclusive breastfeeding in the Harapan Sehat Slawi Hospital Work Area. This type of research is quantitative research with an observational study design. The sampling technique in this research was purposive sampling of 62 people. Statistical tests use frequency distribution, chi square test and multiple logistic regression test. Results the chi square statistical test showed that there was an influence of education p value of 0.000 (< 0.05), employment p value of 0.008, age at risk p value of 0.006 and husband’s support p value of 0.003 on exclusive breastfeeding in the hospital work area Slawi’s Healthy Hope. The factor that most influences exclusive breastfeeding in the Harapan Sehat Slawi Hospital Work Area is husband’s support with a p value of 0.006 and an odds ratio of 363.52. Conclusion: The determinant factor that has the most influence on exclusive breastfeeding is husband’s support.